Diversidad bacteriana en las aguas residuales domésticas de calceta y su relación en la calidad del agua del río Carrizal. Año 2018 - Vera Vera, Beatriz Rocío (2019)
The research "Bacterial diversity in the domestic wastewater of Calceta and the water quality of the Carrizal river. YEAR 2018 ", had as a general objective, to evaluate the relationship between the bacterial diversity present in the domestic wastewater of the city of Calceta and the water quality of the Carrizal River, for this, samples were taken at four key points: the tributary, effluent and two samples in the water body where the treated water flows. Molecular tools such as DNA extraction, PCR and metagenomics were used for the analysis. The sensitivity of these techniques allowed the amplification of 16S rDNA gene fragments from the amplified PCR product. These samples were sequenced, the sequencing being an alternative that provides information on the identity of the microbial population, managing to characterize the structure of an environment, the use of these techniques in turn allowed to determine the water quality of the Carrizal river, this analysis involved In addition to the microorganisms sequenced through metagenomic analysis, indicators such as BOD, fecal and total coliforms. Key words: Bacterial diversity, domestic wastewater, metagenomics, water quality